Apakah Kurikulum Merdeka Mampu Memfasilitasi Pengambangan Karakter Siswa - Maulidya, Sity Rahmy; Sri Ulfa Insani; Zulfah (Jurnal Pustaka Cendekia Pendidikan, 2024)
Merdeka Curriculum is expected to be able to create superior human resources, where students are not only prepared to become intelligent people, but also have strong moral aspects. This literature review was conducted to examine how learning based on the Merdeka Curriculum affects student character development. This research is qualitative descriptive approach. The data for this research is sourced from journal articles, books, as well as observations and interviews to strengthen the author's ideas. This research found that the 6 dimensions of the Character of Pancasila Students (Profil Pelajar Pancasila) are able to facilitate student character development. The habit of always presenting character values and competencies from the Character of Pancasila Students is able to have a good impact on student character building. The overall goal of intracurricular, co-curricular and extracurricular activities is to make students have Character of Pancasila Students. The results of observations and interviews also show that competencies and character has been running well and successfully carried out on students at school and continues to be pursued to be optimal.